Catching up and falling behind: Four puzzles after two decades of post-communist transformation - Zenonas Norkus (Comparative Economic Research. Central and Eastern Europe, 2015)
After more than two decades since the exit from Communism, no former communist country has been completely successful in catching up with the technological frontier countries. However, they divide into two groups: those which decreased the GDP gap with frontier countries since 1989-1990, and those which failed to do so. One may ask: What were the decisive causal conditions for their progress or failure in convergence? Were they the early implementation of Washington consensus style market reforms; their neighbourhood with advanced affluent countries; peaceful transition; accession to the EU; endowment with natural resources; state sovereignty before postcommunism; or interactions between these factors (or others)? Because of the small N, statistical analysis is not an appropriate tool for testing these hypotheses. Hence this paper uses qualitative comparative analysis to identify four explanatory puzzles of the catching-up growth performance of the postcommunist countries.
Keywords: 330; post-communism; catching up growth; qualitative comparative analysis; market reforms; location; EU membership; war; natural resources; statehood